Volcanic ash analyses in sediments of ODP Leg 201 sites - D Hart; D Jay Miller (PANGAEA, 2006)
Although land studies have identified major volcanic centers of historic eruptions within the Central Andes, the tephrachronologic record is disturbed by the high erosion rates in this arid region. Owing to erosion, studies of volcanic cyclicity based on subaerial deposits offer an incomplete record of the frequency and episodicity of eruptions since the Miocene. However, volcanic material commonly occurs in marine sediment as discrete ash fall layers and/or disseminated ash accumulations. A detailed investigation of cores from three sites offshore Peru drilled during Ocean Drilling Program (ODP) Leg 201 has been conducted to determine the occurrence of volcanic ash layers and ash accumulations within marine sediments along the Peru shelf. These sites were previously occupied during ODP Leg 112, which suffered from poor and/or disturbed core recovery. Advancements in hydraulic piston coring realized since and employed during Leg 201 resulted in better core recovery and less disturbance of sediment throughout the cored intervals. Because marine sediments potentially undergo less erosion than land deposits and because Leg 201 benefited from improved recovery of less disturbed cores, the tephrachronologic record from Leg 201 yielded a more complete record of explosive activity for north-central Andean volcanism than previous studies. Ash layers were identified through detailed core descriptions supplemented by smear slide analysis. Primary ash layers were confirmed through whole-rock and glass geochemistry and petrographic analyses. These data also provided information concerning volcanic episodes represented by the ash layers through correlation to land studies. In addition, correlative ties between drilling sites are suggested. The improved recovery enabled the detailed examination of cores from the Peru margin needed to test the hypothesis that volcanic ash layers and accumulations are more abundant in the study region than previously reported.
Supplement to: Hart, D; Miller, DJ (2006): Analysis and correlation of volcanic ash in marine sediments from the Peru margin, Ocean Drilling Program Leg 201: explosive volcanic cycles of the north-central Andes. In: Jørgensen, BB; D extquotesingleHondt, SL; Miller, DJ (eds.) Proceedings of the Ocean Drilling Program, Scientific Results, College Station, TX (Ocean Drilling Program), 201, 1-43, https://doi.org/10.2973/odp.proc.sr.201.122.2006